2020
DOI: 10.1016/j.athoracsur.2020.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Venovenous Extracorporeal Membrane Oxygenation Without Systemic Anticoagulation

Abstract: Background-Venovenous extracorporeal membrane oxygenation (ECMO) is increasingly being used for acute respiratory distress syndrome and as a bridge to lung transplantation. After initiation of venovenous ECMO, systemic anticoagulation therapy is traditionally administered and can cause bleeding diathesis. Here, we investigated whether venovenous ECMO can be administered without continuous systemic anticoagulation administration for patients with acute respiratory distress syndrome.Methods-This is a retrospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
87
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(91 citation statements)
references
References 28 publications
2
87
0
2
Order By: Relevance
“…13 Procedures performed on patients such as ECMO may increase blood transfusion needs, although in our hospital avoidance of systemic anticoagulation during ECMO was recently shown to minimize transfusion needs. 21,22 In this preliminary study, we used COVID-19 ward locations as a rapid means to estimate transfusion rates in a large number of patients. This included some patients who were assigned there briefly for clinical suspicion before their tests were negative.…”
Section: Discussionmentioning
confidence: 99%
“…13 Procedures performed on patients such as ECMO may increase blood transfusion needs, although in our hospital avoidance of systemic anticoagulation during ECMO was recently shown to minimize transfusion needs. 21,22 In this preliminary study, we used COVID-19 ward locations as a rapid means to estimate transfusion rates in a large number of patients. This included some patients who were assigned there briefly for clinical suspicion before their tests were negative.…”
Section: Discussionmentioning
confidence: 99%
“…We had two intra-cerebral haemorrhage, both leading to death, and 2 cases of gastrointestinal haemorrhage, of which one required endoscopic intervention. We were able to run the ECMO circuit without anticoagulation for longer than a week without any issue in the patients with gastrointestinal and intra-cerebral haemorrhage; this is a recognised strategy in ECMO patients at high risk of bleeding [17].…”
Section: Anticoagulation and Renal Replacement Therapymentioning
confidence: 99%
“…Conducting venovenous ECMO without continuous systemic anticoagulation has been proposed ( 9 , 10 ). Although confounded by indication bias, recent observational studies suggest that strategies using only prophylactic doses of anticoagulation appear safe in venovenous ECMO ( 9 , 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…Conducting venovenous ECMO without continuous systemic anticoagulation has been proposed ( 9 , 10 ). Although confounded by indication bias, recent observational studies suggest that strategies using only prophylactic doses of anticoagulation appear safe in venovenous ECMO ( 9 , 10 ). Further, a recent systematic review suggested that the rates of thromboembolism and circuit thrombosis among patients who did not receive systemic anticoagulation during venovenous ECMO were comparable with the rates reported among patients treated with systemic anticoagulation ( 11 ).…”
Section: Discussionmentioning
confidence: 99%